Enhancing MSMEs Growth through Halal Product Certification: A Jasser Auda's Maqasid Syari'ah Approach - A. Samsul Ma'arif; Dwi Hidayatul Firdaus (Peradaban Journal of Economic and Business, 2024)
This article analyzes the contribution of halal product certification to the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through the framework of Jasser Auda's Maqasid Shari'ah theory. Departing from conventional studies that focus on technical aspects, this research argues that halal certification, when viewed through Auda's systemic lens, becomes a tool for achieving holistic societal welfare by upholding the core principles of Maqasid. This approach enhances MSME competitiveness, fosters consumer trust, and expands market access. The article advocates for government support and cross-sector collaboration to optimize the implementation of halal certification and build a sustainable halal ecosystem, thus contributing to a more equitable and robust Indonesian economy.